The Effect of Implementing an Accounting System on Profitability in MSMEs in The District Sandpaper Field - Purba, Mila Purnama Sari; Lubis, Kartika Sari (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this research is to determine the effect of implementing an accounting system on profitability in MSMEs in Medan Amplas District. This research uses quantitative data. The data source used is primary. The data collection method uses a questionnaire technique. The population in the study was all 101 culinary MSMEs in Medan Amplas District. And the research sample was 36 MSMEs in the culinary sector that have been established since 2021 and have sales of more than 30 million per year. Data analysis using a simple regression test using SEM on SmartPLS. The research results show that the accounting system has a positive and significant effect on profitability of MSMEs in Medan Amplas District. So, it can be said that if the implementation of the accounting system in the 36 MSMEs in Medan Amplas District gets better, it will increase the profitability of MSMEs in Medan Amplas District. Vice versa. As much as 50.01% of the profitability variable is influenced by the accounting system implementation variable